HAK ASASI PEREMPUAN DALAM HUKUM KELUARGA BERBASIS AL -QUR’AN - Ahmad Chalabi (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2020)
The conclusion of this article is that the human right of women in law.The perspective of the koran is a basic right inheren in women as a gift from God related to norm s and laws that protect women as individual sosial beings and the spritual dimension. Individual women’s right in family law are the right to the right to the opportunity to gain education and achievement, right related to marriege and khulu right and enheritance right. While women’s right as social beings is the right of women to have the opportunity to take part in a balanced manner in the domestic and public sphere, namely the right to work the right to become the leader of entrepreneurial right, security rights, fan comfort in the workplace and social media including getting a healty environment. As well as women’s right as a spritual dimension women also have the right as a spritual dimension women also have the right to worship according to religios provisions and with the dosire and ability no one can deprive women of their right to worship